Add-on ketogenic diet versus antiseizure medications alone in children with developmental and epileptic encephalopathies: a prospective comparative cohort study - Hu, Wandong; Li, Lili; Zhao, Fen; Su, Song; Zhang, Hongwei; Li, Xiaoying (Frontiers in Neurology, 2025)
ObjectiveTo compare the effectiveness and safety of ketogenic diet (KD) versus antiseizure medications (ASMs) adjustment in developmental and epileptic encephalopathy (DEE).MethodsIn this prospective, single-center cohort study, 268 participants were allocated to either the KD group (n = 128) or the control group (n = 140; ASMs adjustment alone). Outcomes were assessed at 3 and 6 months. The primary outcome was the ≥50% seizure response rate at 6 months. Secondary outcomes included seizure-free rates, electroencephalography (EEG) improvements, and developmental progress. Other outcomes included adverse events, retention rate, and predictors of KD response.ResultsAt 6-month evaluation, KD group demonstrated significantly better seizure response than in controls (50.78%vs.29.29%RR = 1.73, 95% CI 1.27–2.36, p < 0.001). The KD group superior in secondary outcomes, including higher seizure-free rates, greater EEG improvement, and better developmental progress. The adverse actions were slight and acceptable. Survival analysis revealed a higher retention rate in KD group than that in control group at any point (HR = 0.68, 95%CI 0.50–0.92, p < 0.05). No significant predictor of KD effectiveness could be found.InterpretationKD demonstrated superior effectiveness and safety over ASMs adjustments in children with DEE, achieving not only reduced seizure frequency and EEG abnormalities but also improved developmental outcome. These findings supported early consideration of KD in DEE management.